Edible Mushrooms as Source of Fibrin(ogen)olytic Enzymes: Comparison between Four Cultivated Species - Tania Petraglia; Tiziana Latronico; Grazia Maria Liuzzi; Angela Fanigliulo; Aniello Crescenzi; Rocco Rossano (Molecules, 2022)
Cardiovascular diseases represent the main cause of death. A common feature of cardiovascular disease is thrombosis resulting from intravascular accumulation of fibrin. In the last years, several fibrinolytic enzymes have been discovered in many medicinal or edible mushrooms as potential new antithrombotic agents. This study aimed to compare the fibrin(ogen)olytic activity of crude extracts from the fruiting bodies of four cultivated edible mushrooms: Lentinula edodes, Pleurotus ostreatus, Pleurotus eryngii, and Agrocybe aegerita. Fibrin(ogen)olytic activity was assessed by fibrin plate, spectrophotometric assay and electrophoretic analysis (SDS-PAGE and zymography). The highest activity was detected for P. ostreatus followed by P. eryngii, L. edodes and A. aegerita. Results indicated that enzymes exhibited maximum activity at pH 6–7 and 30–40 °C, respectively. Enzyme activity was inhibited by serine and metalloprotease inhibitors. We proposed a new index called the Specific Fibrin(ogen)olytic Index (SFI), which allows specification of the proportion of the total proteolytic capacity due to the fibrin(ogen)olytic activity. These data suggest that the extracts from fruiting bodies or powdered mushrooms can be used as functional ingredients for the development of new functional foods that may act as thrombolytic agents responding, at the same time, to the increasing demand for safe, healthy and sustainable food.